1990
DOI: 10.1002/1097-0142(19900701)66:1<130::aid-cncr2820660123>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Etoposideversus etoposide plus high-dose cisplatin in the management of advanced non-small cell lung cancer: Results of a prospective randomized fonicap trial

Abstract: Two hundred sixteen patients with unresectable non-small cell lung carcinoma were randomly allocated to receive etoposide (120 mg/m2, days 1-3) either alone or in combination with high-dose cisplatin (60 mg/mz, days 1-2). The patients' distribution and characteristics were similar in the two treatment arms. The objective response rate for etoposide was 7% versus 25.8% for etoposide plus cisplatin ( P < 0.005). Median progression-free survival in etoposide arm was 3.5 months versus 5 months in the combination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Moreover, in US post-marketing data about vinorelbine, hearing impairment has been reported (Food and Drug Administration, 2014). As far as etoposide was concerned, in a randomized trial, tinnitus and/or hearing loss was present in 24.5% of patients treated with etoposide and cisplatin versus 2.8% of patients in treatment with single-agent etoposide (Rosso et al, 1990). In the disproportionality analysis, we found a statistically significant ROR for drugs used in cardiovascular disorders (beta-blockers, plain ACE inhibitors, RAS-acting agents, selective Ca 2+ channel blockers, and alpha-blockers) but also for the single active substances (propafenone, doxazosin, metoprolol, bisoprolol, nebivolol, ramipril, irbesartan, losartan and diuretics, and hydrochlorothiazide and potassium-sparing agents).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in US post-marketing data about vinorelbine, hearing impairment has been reported (Food and Drug Administration, 2014). As far as etoposide was concerned, in a randomized trial, tinnitus and/or hearing loss was present in 24.5% of patients treated with etoposide and cisplatin versus 2.8% of patients in treatment with single-agent etoposide (Rosso et al, 1990). In the disproportionality analysis, we found a statistically significant ROR for drugs used in cardiovascular disorders (beta-blockers, plain ACE inhibitors, RAS-acting agents, selective Ca 2+ channel blockers, and alpha-blockers) but also for the single active substances (propafenone, doxazosin, metoprolol, bisoprolol, nebivolol, ramipril, irbesartan, losartan and diuretics, and hydrochlorothiazide and potassium-sparing agents).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between cisplatin containing double therapy and monotherapy with the non-platinum agent Results of trials comparing monotherapy with vindesine (Elliott et al, 1984;Einhorn et al, 1986), etoposide (Rosso et al, 1990), teniposide (Splinter et al, 1996), and vinorelbine (Depierre et al, 1994;Le Chevalier et al, 1994) with the respective agent combined with cisplatin showed consistently higher response rates in the combination therapy arm, but only about half showed a survival benefit for the combination (Table 2). Similarly, preliminary analysis of a multicenter phase III trial comparing docetaxel vs docetaxel plus cisplatin in patients with inoperable advanced and metastatic NSCLC showed no survival advantage but a significant improvement in objective response rate with combination therapy (Georgoulias et al, 2002; Table 2).…”
Section: Cisplatin and Carboplatinmentioning
confidence: 99%
“…Longeval and Klastersky used cisplatin and etoposide in 94 patients with advanced NSCLC: A 38% response rate and a median survival of 7.5 months were noted 23. The accumulated response rate of cisplatin and etoposide in 647 patients from 7 trials was 28% (20–30%) 24–30. The median survival times in these 7 studies ranged from 24.5 weeks to 32 weeks.…”
Section: Discussionmentioning
confidence: 99%